ANALISIS KEPUASAN PELANGGAN TERHADAP KUALITAS LAYANAN DI ALFAMART H189 KEDUNGPANE SEMARANG DENGAN METODE SERVICE QUALITY DAN KANO: ANALISIS KEPUASAN PELANGGAN TERHADAP KUALITAS LAYANAN DI ALFAMART H189 KEDUNGPANE SEMARANG DENGAN METODE SERVICE QUALITY DAN KANO - ermayana (Fakultas Teknik dan Rekayasa, 2022)
From year to year there have been many developments in the retail industry, Alfamart H189 Kedungpane as one that must be able to maintain the level of customer satisfaction service so that public interest in visiting remains high. This study aims to determine the quality of service at Alfamart H189 Kedungpane based on the Service quality method and the Kano method. In terms of customer satisfaction, the service quality approach can be applied to measure the level of customer satisfaction. Service quality is measured based on the gap/GAP between perceived performance and expectations. Kano is used to categorize attributes to find out what attributes must be maintained, improved and considered to be able to meet customer satisfaction. The results of research conducted using the Service Quality Method on five dimensions of service quality, namely Tangibles, Reliability, Responsiveness, Assurane and Empathy for GAP 5. It was found that there were still gaps, the largest GAP value was in the Assurance dimension of -0.54. The highest service quality value is found in the Responsiveness dimension of -0.03. Based on the results of the integration of the Service Quality and Kano Methods, it is known that from the 17 variables studied there are 5 variables that are recommended to be maintained, 3 variables are recommended to be improved and 9 variables are recommended to be considered.Keywords: Service Quality, Service Quality Method, Kano Method